Pengembangan Bisnis Toko Wingko “Kelapa Muda” - Kurniawan, Ricky Wijaya; Munir, Ningky Sasanti (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
Development of a business model that provides analysis of weaknesses and takes advantage of opportunities, as well as in-depth information that is evaluated and used for competition in modern markets and the impact of Covid-19. Through the Business Model Canvas (BMC) which maps strategies based on an analysis of strengths, weaknesses, threats and opportunities. The results of the analysis will be redeveloped through the Blue Ocean Strategy (BOS) with the ERRC Grid approach from eliminating, increasing, reducing, and creating. Guided by the